Evaluation of chondrocyte culture in novel airlift bioreactor using computational fluid dynamics tools - Anand A.; Mallick S.P.; Chandel I.S.; Singh B.N.; Srivastava P. (My University, 2025)
This study delineates the design of a novel airlift bioreactor (ALBR) with wavy draft tube, using computational fluid dynamics (CFD) for chondrocyte culture. The advantage of using wavy walled ALBR is that it enhances mass transfer when the optimum superficial gas velocity of 0.5 m sec–1 is applied. To simulate the gas-liquid flow and investigate the effects of wavy shape in the cylindrical draft tube in the internal loop of ALBR, Eulerian model in CFD was used. The correlation was established between the geometry of the ALBR and the hydrodynamics of the broth. The result of the experiment supports the fact that enhanced mixing with controlled shear in the bioreactor leads to better growth of the cell and also, significantly improves the oxygen transfer and mass transfer of nutrients by diffusion. Copyright © 2023 Inderscience Enterprises Ltd.